<teiPublisher>: Bridging the Gap Between a Simple Set of Structured Documents and a Functional Digital Library - SCHREIBMAN, SUSAN (My University, 2004)
Digital Libraries are complex systems that take a long time to create and tailor to specific requirements [1]. Their implementation requires special- ized computer skills, which are not usually found within humanities text encod- ing projects. Many encoders working on text encoding projects find they cannot take their work to the next level by transforming their collections of structured XML [2] texts into a publishable web sear chable and browsable service. Most often these teams find the way to encode their texts with a high degree of so- phistication, but unless they have funds to hire computer programmers their col- lections remain on local disk storage away from public access. is a novel tool designed with the aim of bridging the gap between simply having a collection of structured documents and having a functional digital library for public access via the web. The goal of this project is to build the tools to man- age an extensible, modular and confi gurable XML-based repository which will house, search/browse on, and display doc uments encoded in TEI-Lite [3] on the World Wide Web. provides an administrative interface that al- lows DL administrators to upload and delete documents from a web accessible repository, analyze XML documents to determine elements for search- ing/browsing, refine ontology developmen t, decide on inter and intra document links, partition the repository into collec tions, create backups of the entire re- pository, generate search/browse and di splay pages for users of the website, change the look of the interface, and a ssociate XSL transformation scripts and CSS stylesheets to obtain different ta rget outputs
Lecture Notes in Computer Science
Research and Advanced Technology for Digital Libraries: 8th European Conference, ECDL
PUBLISHED
Keywords: Digital libraries